Boron‐Modified Electron Transfer in Metallic 1T MoSe2 for Enhanced Inherent Activity on Per‐Catalytic Site toward Hydrogen Evolution. Issue 1 (20th November 2019) - Mao, Zeyang; Wang, Chao; Lu, Haoliang; Tang, Kai; Li, Qun; Yan, Chenglin; Wang, Xianfu
Abstract: Phase‐transition‐induced electronic structure and geometry‐modulation‐increased edge sites are of great importance for boosting the electrocatalytic activity of MoSe2 toward hydrogen evolution reaction (HER). However, little efforts have been made to improve the intrinsic activity on per‐catalytic site of MoSe2 for HER. In this work, the electrocatalytic HER activities of MoSe2 are extremely enhanced by simple incorporation of boron which can reasonably engineer the electron transfer from Mo atoms to the active sites including B and Se atoms. Compared with the pristine 1T MoSe2, the as‐opimized B‐1T MoSe2 nanosheets show a reduced overpotential of 180 mV at current density of 10 mA cm −2, a lowered Tafel slope of 50.6 mV dec −1, and increased turnover frequency under a constant overpotential. While the electrochemical surface area of the catalyst after B‐incorporation is decreased, the improved inherent activity on per‐catalytic site and facilitated HER kinetics are demonstrated. The results pave the way to reasonably engineer the electron transfer to the active sites in the catalysts by B‐doping to boost the intrinsic activity on per‐catalytic site for electrocatalytic HER. Abstract : Inherent activity on per‐catalytic site of MoSe2 toward hydrogen evolution is extremely optimized by simple boron incorporation due to the reasonably engineered electron transfer from Mo atoms to the active sites that can greatly reduce the free energy of the hydrogen desorption.